Relationship between job satisfaction and job factors among extension agents in the Malaysia's oil palm industry - Che Jaafar, Nazirah; Man, Norsida; Latib, Alaudin; Aman, Zaki; Moslim, Ramle (Malaysian Palm Oil Board, 2019)
This study was conducted to determine the level of job satisfaction and its relationships with job factors among extension agents involved in Malaysia’s oil palm industry. Data were collected by a census method using self-administered questionnaires from a total of 254 respondents. The Minnesota Satisfaction Questionnaire (MSQ) was used to measure job satisfaction of the respondents. Data were analysed using SPSS version 21.0. The results indicated that the job satisfaction level amongst the extension agents was high. This study also found that there was a significant positive relationship between job satisfaction and job factors, namely salary, promotion opportunities, supervision, co-workers, work environment and the work itself. To ensure continuous job satisfaction amongst extension agents, contributing factors towards job satisfaction should be given attention and maintained by the organisation.